2010
DOI: 10.1007/s11274-010-0618-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification, and biochemical characterization of a brown rot fungus capable of textile dye decolorization

Abstract: Twenty-two local brown rot fungal isolates were obtained from 5 different environmental sources. Fourteen isolates were presumptively identified as Aspergillus sp. and eight as Penicillium sp. using mycelium and spore morphology. All the fungal isolates were screened for their ability to decolorize Isolan Red and colored waste water and to produce oxidase activity. Aspergillus isolate 2 was chosen for further study because it could decolorize both dyes and produce oxidase. A 400 bp fragment of the 18S rRNA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…All primers used for DNA amplification reactions were purchased from Integrated DNA Technologies. Bacillus isolates characterized biochemically were reconfirmed by PCR targeting 16SrRNA (Gomaa and Momtaz 2006). PCR mixture (25 ul) contained, template DNA (5 ll), GoTaq Green Master Mix (12.5ul, Thermo Fisher Scientific, Mumbai, India), nuclease free water (6.5ul, Thermo Fisher Scientific, Mumbai, India), 0.5ul of forward primer (10 pmol/ll), 0.5 ull of reverse primer (10 pmol/ll).…”
Section: Dna Extraction and Amplification Reactionsmentioning
confidence: 99%
“…All primers used for DNA amplification reactions were purchased from Integrated DNA Technologies. Bacillus isolates characterized biochemically were reconfirmed by PCR targeting 16SrRNA (Gomaa and Momtaz 2006). PCR mixture (25 ul) contained, template DNA (5 ll), GoTaq Green Master Mix (12.5ul, Thermo Fisher Scientific, Mumbai, India), nuclease free water (6.5ul, Thermo Fisher Scientific, Mumbai, India), 0.5ul of forward primer (10 pmol/ll), 0.5 ull of reverse primer (10 pmol/ll).…”
Section: Dna Extraction and Amplification Reactionsmentioning
confidence: 99%
“…Correlation between the activities of those two enzymes during the biodecolorization of synthetic dyes was demonstrated also by Lan et al (2006) in experiments on the decolorization of fuchsine and rhodamine B by Phanerochaete chrysosporium ATCC 34541. Gomaa et al (2011) observed that the decolorization effectiveness of a strain of Aspergillus sp. toward Basic Blue increased with increasing activity of glucose oxidase.…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…EL-2 capable of decolorizing textile waste water (Gomaa et al 2011) is used in the following study. The fungus was grown on GYP medium which consisted of glucose (20 g/l); yeast extract (5 g/l); peptone (5 g/l) and magnesium sulfate (1 g/l).…”
Section: Microorganism and Cultivation Conditionsmentioning
confidence: 99%
“…EL-2, characterized in a previous work (Gomaa et al 2011) as a promising and efficient organism in bioremediation of textile waste water, is further investigated in the current work in terms of assessment of the level of toxicity of single and combined treated textile waste water for its potential use in non-potable applications.…”
Section: Introductionmentioning
confidence: 99%